The Effectiveness of Gelugur acid (Garcinia atroviridis) Marinade on the Physical Quality of Culled Chicken Meat - Peni Patriani; Harapin Hafid (Faculty of Animal Science Universitas Brawijaya, 2021)
A method to improve the physical quality of culled chicken meat is required due to the tough texture and faint color of culled chicken meat. High protein content in culled chicken meat makes it easy to experience quality degradation. One of the methods to maintain the quality of post-harvest chicken meat is using spices. Gelugur acid (Garnicia atroviridis) is a spice for cooking spice, sweets, herbs, deodorizing fresh fish, and even cleansing fish before it proceeds into the processing stage. This study aimed to determine the concentration of Garcinia atroviridis which is effective to improve the physical quality of culled chicken meat. This study used a randomized design with 4 treatments and 5 replications. The treatments consisted of T0: without marination using Garcinia atroviridis (as control), T1: marination in 50 g of Garcinia atroviridis + 1000 mL aquadest, T2: marination in 50 g of Garcinia atroviridis + 750 mL aquadest, T3: marination in 50 g of Garcinia atroviridis + 500 mL aquadest. The parameters were the physical quality of meat consisting of meat pH, water holding capacity, tenderness, cooking loss, drip loss and meat color. Based on the results of the study, Garcinia atroviridis marinade had significant effect (P <0.05) on the pH value of the meat, cooking loss, drip loss, tenderness, water holding capacity, and meat brightness. It was concluded that the marination of meat at concentration of 50 g of Garcinia atroviridis + 1000 mL aquadest (T1) was effective in maintaining the pH value, reducing meat drip loss, increasing water holding capacity, increasing tenderness, brightening the color of the meat and maintaining the freshness of the refined culled chicken meat. Marination of meat in concentration of 50 g Garcinia atroviridis + 750 mL aquadest (T2) was also effective in reducing cooking loss of culled chicken meat.